Chemical Bonding: From Simple Bond Forces to Electron Pairs - Hans-Dieter Barke; Nina Harsch (Indonesian Journal of Educational Research and Technology, 2022)
In chemistry, there are two equivalent ways of describing chemical bonding between atoms in a molecule: bond forces and electron pairs. Chemical bonding by bond forces may be introduced already in early chemistry classes – without having relations to the nucleus-shell model of atoms. Standard bonding forces can be defined easily, such as four bonds in the case of the C atom within a CH4 molecule or two bonds in the case of the O atom within an H2O molecule. Accordingly, proposals for chemistry education are discussed and ways of instruction are compared.